2014
DOI: 10.1080/00380768.2014.945390
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of soybean root exudates under phosphorus deficiency

Abstract: Root exudates are derived from plant metabolites and their composition is affected by the plant nutritional status. The purpose of this study was to examine soybean root exudates under phosphorus (P) deficiency using a metabolite profiling technique. Glycine max L. (cv. Suzuyutaka) was grown in a culture solution at P concentrations of 0 (P0) and 8 (P8) mg P L −1 for 1, 5, 10 and 15 days after transplanting. Shoot extract, root extract and root exudates were collected and their metabolites were determined by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 25 publications
(24 reference statements)
4
55
0
Order By: Relevance
“…Nitrogen deficiency did not induce the expression of ICHG in root, suggesting that an ATP-dependent transporter contributes the secretion of isoflavones during the nitrogen deficiency in addition to the ICHG-mediated secretion. In soybeans, the root exudation of amino acids and organic acids was induced by phosphate deficiency, 17) whereas isoflavone secretion was somewhat reduced and the tissue isoflavone contents were not significantly altered.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nitrogen deficiency did not induce the expression of ICHG in root, suggesting that an ATP-dependent transporter contributes the secretion of isoflavones during the nitrogen deficiency in addition to the ICHG-mediated secretion. In soybeans, the root exudation of amino acids and organic acids was induced by phosphate deficiency, 17) whereas isoflavone secretion was somewhat reduced and the tissue isoflavone contents were not significantly altered.…”
Section: Discussionmentioning
confidence: 96%
“…13,14) Plant growth stages as well as the nutrient deficiency such as nitrogen, phosphate, and iron have been found to significantly affect the secretion of metabolites into the rhizosphere. [15][16][17][18] In rice, for example, the amount of root exudates was the lowest at seedling stage, gradually increased until flowering, and decreased at maturity. 19) In Arabidopsis, metabolites secreted from roots were dynamically altered during development, in correlation with the transcriptomes of rhizosphere microbial communities.…”
mentioning
confidence: 98%
“…Secondly, root exudates play a critical role in the transformation of nCeO 2 in plants. We extracted the root exudates from the plants according to a previously described method, 27 and found that the hydrodynamic sizes of nCeO 2 in root exudate solutions varied among the four plant species (Fig. S8 and S9 †).…”
Section: Rootmentioning
confidence: 99%
“…Root exudates are composed of low molecular compounds such as saccharides, organic acids, amino acids, phenols, high molecular polysaccharides and proteins. 27 The low molecular organic acids (e.g., succinic acid and malic acid) 8 and reducing substances such as phenols, 28 which are critical for the transformation of nCeO 2 , varied among different species. Moreover, different acids and reducing substances have different capacities to dissolve the nCeO 2 .…”
Section: Rootmentioning
confidence: 99%
“…It is also found in relation to anthocyanin accumulation in the skin of red apples (Fernández-Trujillo et al 2001;Noro et al 1988). However, it has rarely been studied in the context of root exudation (Khorassani et al 2011;Tawaraya et al 2014). It has been found to solubilise sparingly available P through ligand exchange, but was reported to be less effective than citrate (Khorassani et al 2011).…”
Section: Introductionmentioning
confidence: 99%